SMART CITIES IN THE FUNCTION OF CRIME PREVENTION - Dimovski, Darko T (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Starting from the problems of modern cities, the author pointed out that one of the ways to solve the resistance of crime to the usual prevention measures is the use of smart cities. After defining the concept of smart cities, the author paid special attention to the analysis of one of its functions - crime prevention. Therefore, in the next part of the work, he presented how far certain local communities have come in the implementation of smart cities with the aim of fighting against the commission of criminal acts. The last part of the paper is dedicated to considering how far cities in the Republic of Serbia have come with the implementation of the smart city concept.